Clinical features and risk factors for mortality in patients with open pelvic fracture: A retrospective study of 46 cases. (21st July 2020) - Guo, Qingshan; Zhang, Letian; Zhou, Siru; Zhang, Zhiyang; Liu, Huayu; Zhang, Lianyang; Talmy, Tomer; Li, Yang
Background: This study aimed to investigate the clinical features, current management strategies, and outcomes of open pelvic fracture patients. Methods: We performed a retrospective review of data on patients with blunt trauma and open pelvic fractures admitted to our trauma center over a 5-year period (January 2013 to December 2017). Demographic as well as clinical data including injury mechanism, injury severity score (ISS), fracture classifications, transfusion requirements, interventions, length of hospital and intensive care unit (ICU) stay, and prognosis were investigated. Univariate analysis and binary logistic regression were used to identify the risk variables of death. Finally, a brief literature review was performed to understand the current capacity of treatment and prognosis of this type of injury. Results: Forty-six patients (36 male and 10 female) were included in this study, mean age 43.2 ± 14.2 years. The overall mortality rate was 17.4%; 43.5% of the patients were hypotensive (systolic blood pressure (SBP) <90 mmHg) on arrival. The average ISS was 31.7 ± 6.7, and the average packed red blood cell (PRBC) transfusion during the first 24 h was 9.6 ± 7.4 units. Five patients (10.9%) underwent transcatheter arterial embolization in the early stage of management. The average hospital and ICU length of stay were 53.0 ± 37.6 days and 14.3 ± 15.3 days, respectively. Statistically significant differences were found in ISS, PRBC units received with the first 24 h, SBP, lactate and base excess on admission, and mechanism of injury when comparing between the death and the survival groups ( p < 0.05). ISS and lactate on admission were found to be the independent risk factors for mortality. Conclusion: The mortality rate of open pelvic fractures remains high. ISS and lactate on admission were the independent risk factors for mortality. Optimization of the trauma care algorithms for early identification and treatment of this injury could be the key to decreasing mortality.